Sustainable water management for irrigated agriculture in Rwanda: systematic narrative review - Ikundabayo, Sonia; Bazimenyera, Jean de Dieu; Bagaragaza, Romuald; Ngarukiyimana, Jean Bosco (Brazilian Journal of Science, 2026)
Sustainable water management is fundamental to the performance of irrigated agriculture in Rwanda, where irrigation plays a critical role in food security, rural livelihoods, and national economic development. Over the past two decades, the Government of Rwanda has made substantial investments in irrigation infrastructure and policy initiatives, notably the Rwanda Irrigation Master Plan (RIMP) and the Strategic Plan for the Transformation of Agriculture (PSTA). Despite these efforts, irrigation coverage and water use efficiency remain below their estimated potential. Of the approximately 600,000 hectares considered suitable for irrigation, only about 10% is currently developed. This systematic narrative review synthesizes peer-reviewed and grey literature published between 2010 and 2025 to assess the status of irrigation systems, water management practices, institutional arrangements, environmental challenges, and emerging technological options in Rwanda. The review shows that around 148 irrigation schemes have been established across marshlands, hillsides, and valley bottoms; however, many schemes are constrained by underutilized infrastructure, sedimentation, high energy costs, limited farmer technical capacity, and weak operation and maintenance mechanisms. Surface irrigation remains the dominant practice, often associated with substantial water losses, while more efficient technologies such as drip and sprinkler systems demonstrate better performance but face low adoption due to financial and technical barriers. Integrated Water Resources Management (IWRM) is increasingly promoted as a guiding framework, emphasizing coordinated water allocation, social equity, and environmental sustainability. Nonetheless, persistent issues such as soil degradation, waterlogging, and inefficient resource use indicate gaps in governance, monitoring, and enforcement. Overall, the review highlights that achieving sustainable water management in Rwanda’s irrigated agriculture will require strengthening institutional capacity, expanding farmer training, scaling up efficient irrigation technologies, and reinforcing IWRM implementation at catchment and scheme levels. These measures are essential for improving productivity, enhancing resilience to climate variability, and safeguarding long-term environmental sustainability.